Low‐light image enhancement with strong light weakening and bright halo suppressing. Issue 3 (31st January 2019) - Tang, Chaoying; Wang, Yeru; Feng, Huajun; Xu, Zhihai; Li, Qi; Chen, Yueting
Abstract : Low‐light enhancement methods suffer from the over‐enhancement problem which could induce the loss of the important texture and make images look unnatural. Moreover, some low‐light images contain strong light areas that must be weakened to improve the visual effect. In this study, an enhancement method with strong light weakening and bright halo suppressing is presented. Firstly, the bright channel prior is applied to the inverted image to weaken the strong light both in and around the strong light areas. Then, a dehazing‐type of algorithm with the dark channel prior is employed via superpixel segmentation to enhance the low‐light image. Finally, a revised non‐local denoising method is proposed to further refine the enhanced image. Experimental results showed that the proposed method achieved better visual effects compared with other state‐of‐the‐art methods. Besides, the quantitative evaluation showed that the authors' method outperforms the other methods both in the aspect of enhancement and denoising.